Improving Speaking Skills through Providing Sentence Starters and Incorporating Images - Sharon Maria Magdalena Purba; Leil Badrah Zaki (Journal of English Language Learning, 2021)
This Classroom Action Research (CAR) was conducted based on an internship of teaching two English Enrichment classes, involving 25 students of Grade 7 in Sekolah Kallista to determine the effectiveness of Providing Sentence Starters and Incorporating Images activities as a part of the Communicative Language Teaching (CLT) method. The research was organised through several procedures, such as designing, implementing, observing, analysing, and presenting. The instruments used were observation, pre-test, and post-test. The students in both classes were first observed and then involved in a series of pre-test, implementation, and post-test so that their improvements could be measured properly using a rubric that assessed their fluency, pronunciation and accent, vocabulary, grammar, content organisation and development, and the duration of their speech as the aspects of speaking skills. Results of the post-test showed that the scores of the students increased from their pre-test scores, proofing that the implementation was effective in supporting students' improving their speaking skills, as well as providing them with an enjoyable atmosphere in learning and allowing them to express creativity throughout the lesson.